Christian Ethical Review of Royalty Collection for the Use of Religious Songs in Online Worship - Laheba, Timothy Rey; Gulo, Yabes Darling; Simanjuntak, Ferry (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: Online worship has rapidly emerged as a prevalent ministry approach in recent years. Many churches opt for broadcasting services via YouTube for virtual worship. However, challenges arise as songwriters request royalties for their songs featured in these online worship broadcasts. This can curtail song selection, consequently impacting service quality for congregants. This study explores the Christian ethical dimensions of royalty collection for religious songs in online worship, utilizing a literature review methodology. Its goal is to offer theological guidance to both songwriters and churches. The research scrutinizes influential academic journals, conducts a comprehensive analysis of biblical principles, and assesses Indonesia's relevant regulations. The primary aim of this study is to establish an ethical Christian perspective for composers and the church when addressing the intricate matter of royalty imposition when using religious songs in online worship. Although labor is a divine command for meeting human needs, Christians perceive work as an avenue to glorify God. Hence, seeking royalties for religious songs used in online worship might not align with this principle. This notion resonates with the non-commercial essence of worship. Moreover, it is imperative for churches to ensure that worship videos disseminated through platforms like YouTube and other social media retain their sanctity by avoiding monetization and commercialization.Â Keywords: online worship, religious song, royalty